Molecular Characterization of PauR and Its Role in Control of Putrescine and Cadaverine Catabolism through the γ-Glutamylation Pathway in Pseudomonas aeruginosa PAO1 - Chou, Han Ting (American Society for Microbiology, 2013)
Pseudomonas aeruginosa PAO1 grows on a variety of polyamines as the sole source of carbon and nitrogen. Catabolism of polyamines is mediated by the γ-glutamylation pathway, which is complicated by the existence of multiple homologous enzymes with redundant specificities toward different polyamines for a more diverse metabolic capacity in this organism. Through a series of markerless gene knockout mutants and complementation tests, specific combinations of pauABCD (polyamine utilization) genes were deciphered for catabolism of different polyamines. Among six pauA genes, expression of pauA1, pauA2, pauA4, and pauA5 was found to be inducible by diamines putrescine (PUT) and cadaverine (CAD) but not by diaminopropane. Activation of these promoters was regulated by the PauR repressor, as evidenced by constitutively active promoters in the pauR mutant. The activities of these promoters were further enhanced by exogenous PUT or CAD in the mutant devoid of all six pauA genes. The recombinant PauR protein with a hexahistidine tag at its N terminus was purified, and specific bindings of PauR to the promoter regions of most pau operons were demonstrated by electromobility shift assays. Potential interactions of PUT and CAD with PauR were also suggested by chemical cross-linkage analysis with glutaraldehyde. In comparison, growth on PUT was more proficient than that on CAD, and this observed growth phenotype was reflected in a strong catabolite repression of pauA promoter activation by CAD but was completely absent as reflected by activation by PUT. In summary, this study clearly establishes the function of PauR in control of pau promoters in response to PUT and CAD for their catabolism through the γ-glutamylation pathway.